An enhanced proton exchange membrane with a single-sided three-dimensional concave-convex surface and a preparation method thereof

By forming a unilateral three-dimensional concave and convex surface structure on the proton exchange membrane and introducing a polymer porous reinforcement framework, the problem of insufficient contact area caused by flat surface of the existing proton exchange membrane is solved, and the fuel cell output performance and mechanical strength are enhanced.

CN115732728BActive Publication Date: 2025-03-25SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211564272.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-03-25
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

The flat surface of the existing proton exchange membrane results in a limited contact area between the catalyst and the membrane, limiting the output performance of the fuel cell, and making it difficult to achieve both mechanical enhancement and interface modification.

Method used

By placing a polymer porous reinforcement framework film on the perfluorosulfonic acid resin solution, a one-sided three-dimensional concave and convex surface structure is formed using the penetration of the solution, the contact area between the film and the catalyst is increased, and the reinforcement framework is introduced to improve mechanical strength.

Benefits of technology

The contact area between the proton exchange membrane and the cathode catalyst is effectively improved, the output performance of the fuel cell is improved, and the stability of the membrane is improved through mechanical enhancement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115732728B_ABST
    Figure CN115732728B_ABST
Patent Text Reader

Abstract

The present invention discloses an enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface and a preparation method thereof. Specifically, a layer of sulfonic acid resin solution is coated on a substrate, and then a polymer film reinforcement skeleton is laid flat on the sulfonic acid resin solution. After heat treatment, an enhanced proton exchange membrane having a naturally formed single-sided three-dimensional concave-convex surface structure is obtained. The operation steps of the present invention are simple. Compared with the conventional sandwich structure reinforcement membrane process, the process naturally constructs a surface with a single-sided three-dimensional concave-convex structure by biasing the polymer film reinforcement skeleton. Using the surface as the cathode side and spraying the catalyst can increase the interface contact area between the catalyst on the cathode side and the proton exchange membrane, thereby increasing the reaction area and utilization efficiency of the catalyst, reducing the interface contact impedance, and improving the fuel cell performance. The invention aims to develop a proton exchange membrane for improving the output performance of fuel cells for fuel cell applications, and has good promotion prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and relates to a proton exchange membrane and a preparation method thereof, and in particular to an enhanced proton exchange membrane with a single-sided three-dimensional concave-convex surface and a preparation method thereof. Background Art

[0002] In fuel cells, the proton exchange membrane plays the role of transferring protons, insulating electrons, and isolating the reactant gas. Its performance directly determines the power output performance, stability, and life of the fuel cell. The proton exchange membrane widely used in the commercial industry is Nafion. TM , etc. series of perfluorosulfonic acid proton exchange membranes. At present, the mainstream method for preparing membrane electrodes based on proton exchange membranes is the CCM (Catalyst Coated Membrane) method of catalyst-coated membranes, that is, the catalyst is deposited on the flat surface of the proton exchange membrane by scraping or spraying. In view of the flat surface of the existing proton exchange membrane, the interface contact between the catalyst layer and the membrane is a two-dimensional plane contact, which leads to a limited contact area between the catalyst and the membrane, resulting in a low utilization rate of the catalyst, which in turn limits the output performance of the fuel cell. Considering that the cathode oxygen reduction reaction is more difficult than the anode reaction, the membrane-catalyst interface of the cathode has a greater impact on the performance of the fuel cell.

[0003] In order to improve the interface bonding between the membrane and the catalyst, studies have reported the use of elastomer mold casting technology to prepare proton exchange membranes with patterned surfaces [Jeon, Yukwon, et al. Scientific Reports, 2015, 5 (1): 16394]. However, the problem with this type of technology is that it requires the pre-preparation of a mold with a fine pattern, which is costly and has low film-forming efficiency. In addition, it is difficult to mechanically reinforce the membrane at the same time, which cannot meet the current application requirements of fuel cells. Therefore, a simple and efficient membrane interface modification technology that includes a reinforced skeleton is urgently needed to be developed. Summary of the invention

[0004] In view of the defects of the above-mentioned prior art, the present invention provides an enhanced proton exchange membrane with a single-sided three-dimensional (3D) concave-convex surface and a preparation method thereof. The present invention places a layer of polymer porous enhanced skeleton film on a layer of sulfonic acid resin solution, and naturally forms a 3D concave-convex surface structure on the surface of the porous skeleton through the penetration of the solution. Based on this type of membrane, the membrane electrode is prepared by the CCM method. Compared with the conventional sandwich structure enhanced membrane with a two-dimensional (2D) smooth surface, the present invention effectively increases the contact area between the proton exchange membrane and the cathode catalyst, improves the reaction area and utilization efficiency of the cathode catalyst, reduces the interface contact impedance, and thus improves the output performance of the fuel cell. At the same time, the enhanced skeleton introduced also plays a mechanical reinforcement role. In the present invention, a single-sided three-dimensional (3D) concave-convex surface is obtained while preparing the enhanced proton exchange membrane. The preparation process is simple and stable, suitable for mass production, and has application prospects.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] The present invention relates to a method for preparing an enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface, the method comprising the following steps:

[0007] S1, coating a layer of perfluorosulfonic acid resin solution on the substrate;

[0008] Alternatively, a layer of perfluorosulfonic acid resin solution is coated on the substrate, followed by covering the surface of the perfluorosulfonic acid resin solution with a layer of a polymer porous reinforced skeleton film, and then coating another layer of perfluorosulfonic acid resin solution;

[0009] S2, then covering the surface of the coated perfluorosulfonic acid resin solution with a layer of polymer porous reinforced skeleton film;

[0010] S3. After drying and annealing, an enhanced proton exchange membrane with a naturally formed single-sided three-dimensional concave-convex surface structure is obtained.

[0011] As an embodiment, the solvent of the perfluorosulfonic acid resin solution is a combination of one or more of n-propanol, deionized water, and dimethylacetamide.

[0012] As an embodiment, the concentration of the perfluorosulfonic acid resin solution is 5-30wt%. The concentration of the perfluorosulfonic acid resin solution is a key parameter for obtaining a reinforced proton exchange membrane with a naturally formed single-sided three-dimensional concave-convex surface. If the concentration of the sulfonic acid resin solution is too low, the sulfonic acid resin solution will diffuse into the membrane surface, resulting in a smooth membrane surface; if the concentration of the sulfonic acid resin solution is too high, the solution will have difficulty in penetrating and diffusing into the ePTFE surface, resulting in a concave-convex surface but lack of sulfonic acid resin, making it difficult to conduct protons. The preferred concentration of the perfluorosulfonic acid resin solution is 10-25wt%, and the more preferred concentration of the sulfonic acid resin solution is 10wt%.

[0013] As an embodiment, the polymer porous reinforced skeleton film is an expanded polytetrafluoroethylene (ePTFE) microporous membrane.

[0014] As an embodiment, the polymer porous reinforced skeleton film has a thickness of 3 to 20 μm and a porosity of more than 50%.

[0015] As an embodiment, the substrate is one of a glass plate and a polyethylene terephthalate (PET) film.

[0016] As an embodiment, the solution coating method is one of a blade coating method and a slit coating method.

[0017] As an embodiment, in step S2, the drying conditions are a temperature of 80-100°C and a time of 0.25-24h.

[0018] As an embodiment, in step S2, the annealing treatment conditions are a temperature of 120-150° C. and a time of 10-120 min.

[0019] The enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface prepared by the method of the present invention also belongs to the protection scope of the present invention.

[0020] The present invention first coats a perfluorosulfonic acid resin solution on a substrate, and then places a polymer porous reinforced skeleton film. The perfluorosulfonic acid resin solution penetrates into the microporous layer of the polymer porous reinforced skeleton film, diffuses upward and covers the polymer porous reinforced skeleton. After drying, a 3D concave-convex surface structure of the perfluorosulfonic acid resin covering the polymer porous reinforced skeleton is formed on the surface of the membrane, thereby increasing the single-side surface area of ​​the membrane, so that when a fuel cell membrane electrode is subsequently prepared, the contact area between the uneven surface and the catalyst is increased, that is, the reaction active area is increased, thereby improving the output performance of the fuel cell.

[0021] Compared with the prior art, the present invention has the following beneficial technical effects:

[0022] (1) The present invention places a layer of polymer porous reinforced skeleton film on the perfluorosulfonic acid resin solution. The perfluorosulfonic acid resin solution relies on the porous skeleton to naturally form a 3D concave-convex surface structure on the membrane surface. Based on this type of membrane, the membrane electrode is prepared by the CCM method. Compared with the conventional sandwich structure reinforced membrane with a 2D smooth surface, the contact area between the proton exchange membrane and the cathode catalyst is effectively increased, the reaction area and utilization efficiency of the cathode catalyst are improved, the interface contact impedance is reduced, and the fuel cell performance is improved; at the same time, the introduced reinforced skeleton also plays a mechanical reinforcement role.

[0023] (2) The preparation process of the conventional enhanced proton exchange membrane is to coat a layer of perfluorosulfonic acid solution on the substrate, then cover the polymer porous reinforcement skeleton, and finally coat another layer of perfluorosulfonic acid solution, and form a sandwich structure after heat treatment, that is, the polymer porous reinforcement skeleton is located in the middle of the membrane, and both sides are perfluorosulfonic acid resin layers with smooth surfaces, forming a conventional enhanced proton exchange membrane structure. The present invention is determined to make progress, by coating a perfluorosulfonic acid solution on the substrate, then covering the polymer porous reinforcement skeleton, and obtaining a single-sided three-dimensional (3D) concave-convex surface structure (the other side contacting the substrate is a smooth surface) enhanced proton exchange membrane after heat treatment.

[0024] (3) Compared with the technology of using complex and expensive patterned templates to cast membranes to form concave-convex surfaces, the present invention obtains a single-sided three-dimensional (3D) concave-convex surface by natural molding while preparing the enhanced proton exchange membrane. The preparation process of the present invention is simple and stable, suitable for mass production, and has application prospects.

[0025] (4) For the enhanced proton exchange membrane also having a single layer of ePTFE, compared with the conventional sandwich structure enhanced membrane process, the process of the present invention reduces one step while forming a surface with a single-sided 3D concave-convex structure, that is, reduces the step of re-coating the perfluorosulfonic acid resin solution, thereby improving the preparation efficiency and reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0027] Figure 1 It is a surface scanning electron microscope photograph; Figure 1 (a) is a surface scanning electron microscope photograph of an enhanced proton exchange membrane (Comparative Example 1) having smooth surfaces on both sides prepared by conventional technology; Figure 1 (b), (c), and (d) are surface scanning electron microscope photographs of enhanced proton exchange membranes with single-sided concave-convex surfaces prepared by the scheme of the present invention (Examples 1, 2 and Comparative Example 2).

[0028] Figure 2 It is a cross-sectional scanning electron microscope photograph; Figure 2 (a) is a cross-sectional scanning electron microscope photograph of an enhanced proton exchange membrane (Comparative Example 1) having smooth surfaces on both sides prepared by conventional technology; Figure 2 (b), (c), and (d) are cross-sectional scanning electron microscope photographs of the enhanced proton exchange membranes (Examples 1, 2, and Comparative Example 2) having a single-sided concave-convex surface prepared by the scheme of the present invention.

[0029] Figure 3A comparison chart of single cell polarization curves of an enhanced proton exchange membrane with smooth surfaces on both sides prepared by conventional technology (Comparative Example 1) and an enhanced proton exchange membrane with a concave-convex surface on one side prepared by the solution of the present invention (Examples 1, 2 and Comparative Example 2).

[0030] Figure 4 AC impedance spectra of single cells of an enhanced proton exchange membrane with smooth surfaces on both sides prepared by conventional technology (Comparative Example 1) and an enhanced proton exchange membrane with a concave-convex surface on one side prepared by the solution of the present invention (Examples 1, 2 and Comparative Example 2).

[0031] Figure 5 A comparison chart of the catalyst surface active area of ​​a single cell of an enhanced proton exchange membrane with smooth surfaces on both sides prepared by conventional technology (Comparative Example 1) and an enhanced proton exchange membrane with a concave and convex surface on one side prepared by the solution of the present invention (Examples 1, 2 and Comparative Example 2).

[0032] Figure 6 Schematic diagrams of the structures of an enhanced proton exchange membrane with smooth surfaces on both sides prepared by conventional technology (Comparative Example 1), an enhanced proton exchange membrane with a concave-convex surface on one side prepared by the scheme of the present invention (Examples 1, 2 or 4), and an enhanced proton exchange membrane with a concave-convex surface on one side prepared by the scheme of the present invention (Example 3). DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0034] In the following examples, the materials and instruments used are commercially available unless otherwise specified.

[0035] Example 1

[0036] This embodiment relates to an enhanced proton exchange membrane having a naturally formed concave-convex surface on one side and a preparation method thereof, comprising the following steps:

[0037] (1) taking a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20 wt%), and diluting it to obtain a 10 wt% perfluorosulfonic acid resin solution;

[0038] (2) coating a layer of perfluorosulfonic acid resin solution (10 wt %) on a glass substrate using a scraper with a scraper gap of 360 μm;

[0039] (3) a layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm) is covered on the surface of the perfluorosulfonic acid resin solution;

[0040] (4) Then drying at 80°C for 12h and thermal annealing at 150°C for 15min. Finally, an enhanced proton exchange membrane with a naturally formed concave-convex surface structure on one side is obtained.

[0041] Example 2

[0042] This embodiment relates to an enhanced proton exchange membrane having a naturally formed concave-convex surface on one side and a preparation method thereof, comprising the following steps:

[0043] (1) taking a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20wt%);

[0044] (2) coating a layer of perfluorosulfonic acid resin solution (20 wt %) on a glass substrate using a scraper, with a wet film thickness of 180 μm;

[0045] (3) a layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm) is covered on the surface of the perfluorosulfonic acid resin solution;

[0046] (4) Then, the mixture was dried at 80°C for 12 h and thermally annealed at 150°C for 15 min. Finally, an enhanced proton exchange membrane with a single-sided concave-convex surface structure was obtained.

[0047] Example 3

[0048] This embodiment relates to an enhanced proton exchange membrane having a naturally formed concave-convex surface on one side and a preparation method thereof, comprising the following steps:

[0049] (1) taking a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20 wt%), and diluting it to obtain a 10 wt% perfluorosulfonic acid resin solution;

[0050] (2) coating a layer of perfluorosulfonic acid resin solution (10 wt%) on a glass substrate with a scraper, with a scraper gap of 100 μm; subsequently, covering the surface of the perfluorosulfonic acid resin solution with a first layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm); then, coating another layer of perfluorosulfonic acid resin solution (10 wt%) on the surface of the ePTFE film, with a scraper gap of 200 μm;

[0051] (3) Covering the surface of the perfluorosulfonic acid resin solution with a second layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm)

[0052] (4) Then, the membrane was dried at 80°C for 12 hours and thermally annealed at 150°C for 15 minutes. Finally, a reinforced proton exchange membrane with a single-sided concave-convex surface structure was obtained, and the membrane body had two ePTFE reinforcement layers.

[0053] Example 4

[0054] This embodiment relates to an enhanced proton exchange membrane having a naturally formed concave-convex surface on one side and a preparation method thereof, comprising the following steps:

[0055] (1) taking a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20 wt%), and diluting it to obtain a 10 wt% perfluorosulfonic acid resin solution;

[0056] (2) coating a layer of perfluorosulfonic acid resin solution (10 wt %) on a PET substrate using a slot die, with a wet film thickness of 200 μm;

[0057] (3) a layer of ePTFE porous reinforced skeleton film (porosity 80%, thickness 5 μm) is covered on the surface of the perfluorosulfonic acid resin solution;

[0058] (4) Then drying at 80°C for 0.25h and thermal annealing at 120°C for 120min. Finally, an enhanced proton exchange membrane with a single-sided concave-convex surface structure is obtained.

[0059] Comparative Example 1

[0060] In this comparative example, the process steps of preparing an enhanced proton exchange membrane with smooth surfaces on both sides using conventional technology are as follows:

[0061] (1) taking a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20wt%);

[0062] (2) coating a layer of perfluorosulfonic acid resin solution (20 wt%) on a glass substrate using a scraper with a scraper gap of 120 μm;

[0063] (3) a layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm) is covered on the surface of the perfluorosulfonic acid resin solution;

[0064] (4) Again, a layer of perfluorosulfonic acid resin solution (20 wt%) was coated on the surface of the ePTFE film, and the scraper gap was 80 μm;

[0065] (5) Then, the mixture was dried at 80°C for 12 h and thermally annealed at 150°C for 15 min. Finally, an enhanced proton exchange membrane with smooth surfaces on both sides was obtained.

[0066] Comparative Example 2

[0067] In this comparative example, a 30 wt % perfluorosulfonic acid resin solution was used to prepare an enhanced proton exchange membrane having a naturally formed concave-convex surface on one side, and the preparation steps were as follows:

[0068] (1) using a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20 wt%), evaporating the solvent to obtain a 30 wt% perfluorosulfonic acid resin solution;

[0069] (2) coating a layer of perfluorosulfonic acid resin solution (30 wt %) on a glass substrate using a scraper with a scraper gap of 120 μm;

[0070] (3) A layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm) is covered on the surface of the perfluorosulfonic acid solution;

[0071] (4) Then, the mixture was dried at 80°C for 12 h and thermally annealed at 150°C for 15 min. Finally, an enhanced proton exchange membrane with a single-sided concave-convex surface structure was obtained.

[0072] Comparative Example 3

[0073] In this comparative example, a 5 wt % perfluorosulfonic acid resin solution was used to prepare an enhanced proton exchange membrane having a naturally formed concave-convex surface on one side, and the preparation steps were as follows:

[0074] (1) taking a perfluorosulfonic acid resin solution (Nafion D2020, the perfluorosulfonic acid resin concentration is 20 wt%), and diluting it to obtain a 5 wt% perfluorosulfonic acid resin solution;

[0075] (2) coating a layer of perfluorosulfonic acid resin solution (5 wt %) on a glass substrate using a scraper with a scraper gap of 600 μm;

[0076] (3) a layer of ePTFE porous reinforced skeleton film (porosity 78%, thickness 10 μm) is covered on the surface of the perfluorosulfonic acid resin solution;

[0077] (4) Then drying at 80°C for 12 hours and thermal annealing at 150°C for 15 minutes. Finally, an enhanced proton exchange membrane is obtained.

[0078] Performance Tests of Examples and Comparative Examples

[0079] The membrane surface and cross-sectional morphology of the examples and comparative samples were analyzed using a scanning electron microscope (JMS-7800F). Based on the membrane samples, the membrane electrode was prepared using the CCM method, specifically: the catalyst was sprayed on both sides of the membrane, and the Pt loading on the cathode side was 0.4 mg / cm 2 , Pt loading on the anode side 0.1 mg / cm 2 For the sample of the embodiment, the prepared single-sided concave-convex surface is used as the cathode side. The activation area of ​​the assembled single cell is 10 cm2 , the temperature of the single cell was 80°C, and high-purity hydrogen and high-purity air were supplied as reaction gases, respectively, into the anode and cathode of the single cell, and the back pressure was 0.1MPa. The output performance of the fuel cell at 100% RH was tested. At the same time, an electrochemical workstation (Ametek ENERGYLAB-XM) was used to test and compare the AC impedance spectrum (20mV AC signal applied at 0.8V DC voltage) and the catalyst active area (ECSA) of the fuel cell (hydrogen and nitrogen were supplied to the anode and cathode, respectively, and the gas flow rate was 0.08L min -1 Cyclic voltammetry was used with a scan range of 0–1.0 V and a scan rate of 20 mVs -1 The durability of the enhanced proton exchange membrane was evaluated by wet / dry cycle tests and the change in hydrogen permeation current before and after the test. In a typical wet / dry cycle, the duration of 100% humidified nitrogen and dry nitrogen flowing into the single cell was 45s and 30s, respectively. A total of 2000 wet / dry cycles were implemented, and the nitrogen flow rate at the anode and cathode was 0.2L min -1 Before and after the wet / dry cycle test, cyclic voltammetry (scan rate of 1 mV s -1 ) The hydrogen permeation current was tested at 0.3 V, and the hydrogen and nitrogen flow rates at the anode and cathode were both 0.08 L min -1 .

[0080] It should be noted that, during the preparation process, the lower surfaces of the enhanced proton exchange membranes prepared in the embodiments of the present invention and the comparative examples are in contact with the substrate (glass substrate or PET substrate), so the lower surfaces of the enhanced proton exchange membranes prepared have smooth surfaces. Figure 1 (a) is a scanning electron microscope photograph of the upper surface of the enhanced proton exchange membrane prepared by conventional technology in Example 1, showing that the upper surface of the prepared enhanced proton exchange membrane has a smooth surface structure, indicating that it has a smooth surface on both sides. Figure 1 (b), (c), and (d) are scanning electron microscope photographs of the upper surface of the enhanced proton exchange membrane with a single-sided concave-convex surface prepared in Examples 1, 2, and Comparative Example 2, respectively. It can be seen that the prepared enhanced proton exchange membrane has an obvious concave-convex surface structure, indicating that it has a single-sided concave-convex surface.

[0081] Figure 2 (a) is a cross-sectional scanning electron micrograph of a proton exchange membrane prepared by conventional technology in Comparative Example 1, showing a typical sandwich structure, with an ePTFE layer located in the middle of the membrane body and perfluorosulfonic acid resin layers having smooth surfaces on both sides; Figure 2(b) and (c) are cross-sectional scanning electron microscope photos of the proton exchange membrane prepared by the scheme of the present invention in Examples 1 and 2. It can be seen that in the proton exchange membrane, the ePTFE layer is biased to one side of the membrane body, the lower surface has a smooth surface, and the upper surface has a 3D concave-convex surface structure, indicating that the enhanced proton exchange membrane has a single-sided concave-convex surface. The reason for the formation of this unique surface structure is that after the ePTFE microporous layer is covered with the perfluorosulfonic acid solution, the perfluorosulfonic acid solution penetrates into the ePTFE microporous layer, and diffuses upward and coats the ePTFE fiber skeleton. After drying, a 3D concave-convex surface structure of the ePTFE fiber skeleton coated with perfluorosulfonic acid resin is formed on the surface of the membrane body. The concentration of the perfluorosulfonic acid solution is a key parameter for forming a 3D concave-convex surface structure. If the concentration of the perfluorosulfonic acid solution is too high, the viscosity of the solution is too high, such as in Comparative Example 2, Figure 2 As shown in (d), the perfluorosulfonic acid solution is difficult to diffuse to the upper surface layer of the ePTFE fiber skeleton. After drying, the perfluorosulfonic acid resin cannot cover the ePTFE fiber skeleton close to the surface, resulting in a lack of proton conductor on the surface, causing the prepared proton exchange membrane to lack proton conduction throughout the membrane.

[0082] Figure 3 The output performance polarization curves of the single cells assembled with the enhanced proton exchange membranes prepared in Examples 1 and 2 and Comparative Examples 1 and 2 are shown. It can be seen that the peak output power density of the assembled single cell of the enhanced proton exchange membrane with a double-sided smooth surface structure prepared by conventional technology in Comparative Example 1 is 968 mW / cm 2 In Example 1 and Example 2, the enhanced proton exchange membrane with a single-side concave-convex surface structure was prepared by using the scheme of the present invention and based on 10wt% and 20wt% perfluorosulfonic acid solutions, respectively. The peak output power density of the assembled single cells was 1072mW / cm 2 and 1044mW / cm 2 , with higher fuel cell output performance; Comparative Example 3, using the scheme of the present invention, but based on 30wt% perfluorosulfonic acid solution to prepare an enhanced proton exchange membrane, the assembled single cell has a peak output power density of only 644mW / cm 2 , with significantly low fuel cell output performance. This is because the concentration of the perfluorosulfonic acid solution is too high, which makes the solution viscosity too high, and the perfluorosulfonic acid solution is difficult to diffuse to the upper surface of the ePTFE fiber skeleton. After drying, the perfluorosulfonic acid resin cannot cover the ePTFE fiber skeleton near the surface, resulting in a lack of proton conductors on the surface, causing the prepared proton exchange membrane to lack proton conduction throughout the membrane, resulting in a significant increase in the membrane internal resistance of the fuel cell, and thus a significant decrease in the fuel cell output performance.

[0083] Figure 4The AC impedance spectra of single cells assembled with enhanced proton exchange membranes prepared in Examples 1 and 2 and Comparative Examples 1 and 2. In the figure, the high-frequency intercept and the semicircle correspond to the ohmic resistance and the electrode reaction resistance, respectively. Compared with Comparative Examples 1 and 2, the ohmic resistance and the electrode reaction resistance of Examples 1 and 2 are both smaller, resulting in a significantly smaller total resistance. It shows that the 3D concave-convex surface structure prepared by the present invention effectively increases the contact area between the proton exchange membrane and the cathode catalyst, improves the reaction area and utilization efficiency of the cathode catalyst, reduces the interface contact impedance and the electrode reaction resistance, and thus improves the performance of the fuel cell.

[0084] Figure 5 The following is a comparison chart of the catalyst surface active area of ​​a single cell assembled with the enhanced proton exchange membrane made by Examples 1 and 2 and Comparative Examples 1 and 2. It can be seen that compared with Comparative Examples 1 and 2, Examples 1 and 2 have a higher catalyst active area. This is because the proton exchange membrane with a 3D concave-convex surface structure has a larger catalyst contact area. In contrast, the proton exchange membrane with a 2D smooth surface structure has a smaller catalyst contact area. Although Comparative Example 2 has a 3D concave-convex surface structure, because the concentration of the perfluorosulfonic acid resin solution used in the preparation is too high, the perfluorosulfonic acid solution is difficult to diffuse into the upper surface layer of the ePTFE fiber skeleton. After drying, the perfluorosulfonic acid resin cannot coat the ePTFE fiber skeleton close to the surface, resulting in a lack of proton conductors on the surface, resulting in a significant reduction in the active catalytic area.

[0085] By wet / dry cycle test and the change of hydrogen permeation current before and after the test, the durability of the enhanced proton exchange membrane was evaluated. As shown in Table 1, the enhanced proton exchange membrane with a unilateral concave-convex surface prepared by Examples 1, 2, and 4, the wet / dry cycle durability is excellent, and is better than the enhanced proton exchange membrane with smooth surfaces on both sides prepared by conventional technology in Comparative Example 1 and Comparative Example 3 (because the concentration of perfluorosulfonic acid solution is too low, during film making, the solution overflows the ePTFE surface in large quantities, resulting in a smooth and flat membrane surface after drying, similar to Comparative Example 1). The reason why the embodiment performance is better is attributed to the good interface structure between the enhanced proton exchange membrane with a unilateral concave-convex surface and the catalyst layer. In the unilateral concave-convex surface structure, the contact area between the cathode catalyst layer / concave-convex film is expanded. Compared with the interface of the cathode catalyst layer / smooth film, the interface between the cathode catalyst layer / concave-convex film is endowed with a stronger bonding force, which suppresses the delamination and peeling between the catalyst layer and the film. Therefore, using a single cell with a unilateral concave-convex surface enhanced proton exchange membrane, after the wet / dry cycle durability test, the hydrogen permeation current increases less, showing good stability. It is particularly important to point out that the durability of Example 3 with a double-layer ePTFE reinforcement layer is excellent and has the best durability. This is because the increased ePTFE layer further enhances the membrane body and reduces the hydrogen permeation current, so it has better durability. In addition, the wet / dry cycle durability of Comparative Example 2 is the worst, because the concentration of perfluorosulfonic acid solution is too high. When making a film, the solution is difficult to diffuse to the upper surface of the ePTFE fiber skeleton, resulting in a lack of perfluorosulfonic acid resin in the surface after drying, resulting in a large hydrogen permeation current.

[0086] Figure 6 The schematic diagrams are the structures of an enhanced proton exchange membrane with smooth surfaces on both sides prepared by conventional technology (Comparative Example 1), an enhanced proton exchange membrane with a concave-convex surface on one side prepared by the scheme of the present invention (Example 1, Example 2 or Example 4), and an enhanced proton exchange membrane with a concave-convex surface on one side prepared by the scheme of the present invention (Example 3). It can be seen that the preparation idea proposed by the scheme of the present invention is completely different from the traditional scheme.

[0087] The components and properties of the enhanced proton exchange membranes prepared in various embodiments and comparative examples are shown in Table 1.

[0088] Table 1

[0089]

[0090]

[0091] Table 1 Notes:

[0092] ① Fuel cell performance: Excellent (peak power density ≥ 1050mW / cm 2), excellent (1000≤peak power density<1050mW / cm 2 ), good (800 ≤ peak power density < 1000 mW / cm 2 ), poor (peak power density <800mW / cm 2 );

[0093] ②Ohm impedance: Excellent (R total ≤0.3Ωcm -2 ), excellent (0.3<R total ≤0.35Ωcm -2 ), can (0.35<R total ≤0.45Ωcm -2 ), difference (R total >0.45Ωcm -2 ).

[0094] ③Catalyst active area: Excellent (ECSA ≥ 45m 2 g -1 ), good (35≤ECSA<45m 2 g -1 ), can (ECSA<35m 2 g -1 );

[0095] ④ Before and after the wet / dry cycle test, hydrogen permeation current I cross Increase ratio: Excellent (I cross ≤10%), excellent (10%<I cross ≤20%), good (20%<1 cross ≤30%), poor (R total >30%

[0096] In summary, the present invention has simple operation steps. Compared with the conventional sandwich structure enhanced membrane process, the process of the present invention uses a biased polymer film to enhance the skeleton. While preparing the enhanced proton exchange membrane, it naturally constructs a surface with a single-sided 3D concave-convex structure, thereby obtaining an enhanced proton exchange membrane with a single-sided concave-convex surface. Using this surface as a cathode side spray catalyst, with the advantage of high surface area, the interface contact area between the catalyst and the membrane on the cathode side can be increased, thereby improving the utilization efficiency of the catalyst, reducing the interface contact impedance, and improving the output performance of the fuel cell; moreover, for the enhanced proton exchange membrane that also has a single-layer ePTFE, compared with the conventional sandwich structure enhanced membrane process, the process of the present invention is used to form a single-sided 3D concave-convex structure surface, while reducing a process, that is, reducing the process of re-coating the perfluorosulfonic acid resin solution, thereby improving the preparation efficiency and reducing the production cost. It has application potential in improving the output performance of proton exchange membrane fuel cells.

[0097] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other at will.

Claims

1. A method for preparing an enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface for preparing a membrane electrode by a CCM method, characterized in that: The method comprises the following steps: S1. coating a layer of perfluorosulfonic acid resin solution with a wet film thickness of 180 μm, 200 μm or 360 μm on the substrate; S2, then covering the surface of the perfluorosulfonic acid resin solution applied in step S1 with a layer of a polymer porous reinforced skeleton film; the polymer porous reinforced skeleton film is an expanded polytetrafluoroethylene microporous membrane; S3, after drying and annealing treatment, an enhanced proton exchange membrane with a single-sided three-dimensional concave-convex surface structure is obtained; the drying conditions are 80-100° C. and 0.25-24 h; the annealing conditions are 120-150° C. and 10-120 min; The concentration of the perfluorosulfonic acid resin solution is 10-20wt%; the thickness of the polymer porous enhanced skeleton film is 5-20μm, and the porosity is 78%-80%; the other side of the enhanced proton exchange membrane contacting the substrate is a smooth surface; the polymer film in the enhanced proton exchange membrane is enhanced with a biased skeleton; When preparing the membrane electrode, the catalyst is sprayed on both sides of the proton exchange membrane, and the side with the three-dimensional concave-convex surface is the cathode side; and after the ePTFE microporous layer is covered with the perfluorosulfonic acid solution, the perfluorosulfonic acid solution penetrates into the ePTFE microporous layer, diffuses upward and covers the ePTFE fiber skeleton, and after drying, a 3D concave-convex surface structure of the ePTFE fiber skeleton covered with perfluorosulfonic acid resin is formed on the surface of the membrane.

2. The method for preparing an enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface according to claim 1, characterized in that: The solvent of the perfluorosulfonic acid resin solution is a combination of one or more of n-propanol, deionized water and dimethylacetamide.

3. The method for preparing an enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface according to claim 1, characterized in that: The substrate is one of a glass plate and a polyethylene terephthalate film.

4. The method for preparing an enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface according to claim 1, characterized in that: The solution coating method is one of a blade coating method and a slit coating method.

5. An enhanced proton exchange membrane having a single-sided three-dimensional concave-convex surface prepared according to the method of claim 1.

Citation Information

Patent Citations

  • Structures and preparation methods for catalyst coated membranes for fuel cells

    US20170179497A1